2019
DOI: 10.1186/s12885-019-6157-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of lymphocyte-to-monocyte ratio (LMR) and neutrophil-to-lymphocyte ratio (NLR) in patients with oesophageal cancer undergoing concurrent chemoradiotherapy

Abstract: Background and objectivesThe survival rate of patients with advanced oesophageal cancer is very low and can vary significantly, even among patients with the same TNM stage. It is important to look for indicators that are economical and readily available to predict overall survival. The aim of this study was to determine whether lymphocyte-to-monocyte ratio (LMR) and neutrophil-to-lymphocyte ratio (NLR) could be potential predictors of survival in patients with advanced oesophageal squamous cell carcinoma (ESCC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 30 publications
2
55
1
Order By: Relevance
“…31 Studies have shown that markers of systemic inflammation, including the NLR, LMR and PLR, are closely related to the development of tumors. [32][33][34] However, in our study, we found that the increase or decrease in serum NLR, LMR, and PLR were not independent predictors of occult PM of GIST. Therefore, these markers of systemic inflammation were not included during the development of the present model.…”
Section: Discussioncontrasting
confidence: 79%
“…31 Studies have shown that markers of systemic inflammation, including the NLR, LMR and PLR, are closely related to the development of tumors. [32][33][34] However, in our study, we found that the increase or decrease in serum NLR, LMR, and PLR were not independent predictors of occult PM of GIST. Therefore, these markers of systemic inflammation were not included during the development of the present model.…”
Section: Discussioncontrasting
confidence: 79%
“…Routine blood tests are the most common tests performed in pediatric fever clinics and have been used as the primary method for identifying bacterial and viral infections. In recent years, researchers have performed an in-depth analysis of various routine blood parameters, and these parameters are useful for the early diagnosis and prognostic assessment of other diseases [6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…104 NLR is directly associated with the clinical outcome of patients with cancer, which is usually combined with lymphocyte-to-monocyte ratio for evaluation. 105 Sometimes monocyte-neutrophils ratio is also utilized, 106 whereas it is important to have an absolute NLR value for patients to evaluate cancer stage, adequate treatment, and estimate clinical outcome, which would be largely valuable information. Besides, it seems that absolute number of neutrophils might be an underline factor to select the best treatment, which might be a promising index in clinic.…”
Section: Clinical Evaluation By Neutrophilsmentioning
confidence: 99%